The mining legacy in South Africa - a superfund sized problem or a trust fund baby? a critical analysis of the market-based instruments applicable to mining, with specific focus on financial security mechanisms and suggestions for a new approach - Swart, Katherine (Institute of Marine and Environmental Law, 2014)
Includes abstract. Includes bibliographical references.